ITRACONOZOLE THERAPY IN TINEA V ERSICOLOR - Khan, Imranullah; Hameed, Ahsan; Wazir, Shad Muhammad; Shah, Mian Mujahid (Journal of Ayub Medical College Abbottabad, 1999)
The efficacy of itraconazole was assessed in an open trial in 60 patients with wide spread disseminated lesions of Tinea versicolor confirmed by direct microscopy. The patients were allocated randomly to one of the two treatment regimens. 200 mg once daily for 7 days or 100 mg once daily for 15 days. On assessment 3 weeks after the end of the treatment. 50 patients were healed. 4 had mild residual lesions. 4 had considerable residua! lesions, and 2 had relapsed. Two patients reported pain in the abdomen. Two patients reported nausea, vomiting and dyspepsia. Two patients had mild elevation of SOOT, and SOFT. Conclusion: Treatment of tinea versicolor with itraconozole 200mg day for 7 days or l00 mg day for 15 days is recommended.